2012
DOI: 10.1108/08858621211207216
|View full text |Cite
|
Sign up to set email alerts
|

Organized retailing in India: upstream channel structure and management

Abstract: Purpose -This paper's aim is to identify structural and relational factors influencing the upstream channel management of organized retailers in India. Design/methodology/approach -In-depth interviews were conducted with 15 organized retailers and two manufacturers in India. Data were analyzed using the thematic network analysis technique from qualitative research. The authors use the framework of institutional theory to guide the discussion. Findings -The findings suggest that government regulations influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 82 publications
(121 reference statements)
0
4
0
Order By: Relevance
“…Sternquist et al (2008) found that country environment and firm strategy influenced the use of buying committees in China. Sternquist and Chen (2006) found that retailers in China seldom moved out of their current business networks to look for new suppliers, a trend consistent with Indian buyers' reliance on socially embedded network relationships (Srivastava et al , 2012). Studies demonstrate that information processing and decision‐making of industrial buyers varies from country to country and culture to culture (Bonoma et al , 1977; Samli et al , 1988).…”
Section: Literature Reviewmentioning
confidence: 87%
See 1 more Smart Citation
“…Sternquist et al (2008) found that country environment and firm strategy influenced the use of buying committees in China. Sternquist and Chen (2006) found that retailers in China seldom moved out of their current business networks to look for new suppliers, a trend consistent with Indian buyers' reliance on socially embedded network relationships (Srivastava et al , 2012). Studies demonstrate that information processing and decision‐making of industrial buyers varies from country to country and culture to culture (Bonoma et al , 1977; Samli et al , 1988).…”
Section: Literature Reviewmentioning
confidence: 87%
“…Literature on international retail buying in Asia suggests that buying decisions are affected by country‐specific, institutional, and social factors (Srivastava et al , 2012; Sternquist and Chen, 2006; Sternquist et al , 2008). Sternquist et al (2008) found that country environment and firm strategy influenced the use of buying committees in China.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Buying decisions are influenced by country-specific, institutional and social factors (Srivastava et al , 2012; Sternquist and Chen, 2006; Sternquist et al , 2008). Sternquist et al (2008) discovered that a company's strategy and environment determined whether buying teams were utilised in China.…”
Section: The Role Of Fashion Retail Buyers and The Buying Decision-making Processmentioning
confidence: 99%
“…In India, organized retail and unorganized retail compete with each other at various levels. The Indian retail sector is one of the country's top growth industries and, considering its growth, consumers expect more from retail beyond the purchase of a product (Srivastava, 2008;Srivastava Dabas, Sternquist & Mahi, 2012). Indian consumers are also looking to fulfill their hedonic and utilitarian values.…”
Section: Introductionmentioning
confidence: 99%